2019
DOI: 10.21834/aje-bs.v4i13.348
|View full text |Cite
|
Sign up to set email alerts
|

What are Users' Perceptions of the Hospital Courtyard Garden and How Satisfied are they with it?

Abstract: Since the 1970s, courtyard gardens with diverse scales and design configurations have been introduced in the planning of Malaysian public hospitals to enhance users’ experiences. However, these have never been systematically evaluated to understand of how they perform and what improvements can be made to them to increase their responsiveness to users’ needs and inform the practice of both hospital designers and managers. This paper presents the results of fieldwork conducted in a large central c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The results of the study by Georgi and Petros show that hospital users emphasized that they attach importance to roads, recreational areas, social and public areas, personal areas, water views, and a dominant, limited colour range in planting in landscaping [29]. In another study, most of the respondents reported that spending time in the courtyard resulted in them feeling more relaxed and less stressed, more refreshed and rejuvenated, pleased, upbeat, calmer, able to think positively, be comfortable and safe [24]. The results of the study by Whitehouse et al in San Diego in 2001 reflect that children, parents and hospital staff wanted to increase planting around the hospital and to provide more interactive play opportunities for children [28].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of the study by Georgi and Petros show that hospital users emphasized that they attach importance to roads, recreational areas, social and public areas, personal areas, water views, and a dominant, limited colour range in planting in landscaping [29]. In another study, most of the respondents reported that spending time in the courtyard resulted in them feeling more relaxed and less stressed, more refreshed and rejuvenated, pleased, upbeat, calmer, able to think positively, be comfortable and safe [24]. The results of the study by Whitehouse et al in San Diego in 2001 reflect that children, parents and hospital staff wanted to increase planting around the hospital and to provide more interactive play opportunities for children [28].…”
Section: Introductionmentioning
confidence: 97%
“…Study results of Barnhart, Perkins, and Fitzsimonds show a consistent and strong preference for natural environments between patient and staff groups, especially when linked to certain preferred behaviour [23]. In a study conducted by Idris et al, it was concluded that factors affecting the staff, patients and visitors spending time in the hospital garden are the desire to relax and rest in a natural environment, to refresh their minds, and temporarily stay away from the hospital environment [24]. The results of the study conducted by Naderi and Shin with 61 nurses also showed the desire of the staff to communicate with nature and have privacy [25].…”
Section: Introductionmentioning
confidence: 98%
“…Courtyards are climatically responsive areas that instigate the cooling effect for buildings in hot and humid climate areas (Nugroho et al, 2020) and provide indoor ventilation and daylighting to hospitals (Yoon & Lim, 2020). In addition to its functions as a passive design strategy, the hospital courtyard garden (HCG) has essential means of providing a place for staff, patients, and family members to respite and have a connection with nature (Idris et al, 2019). Integration of both the environmental and restorative functions into courtyard design in today's contemporary hospital buildings is critical to effectively meeting the needs of the various users (Idris, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Courtyard gardens were incorporated into the built form of hospital buildings not only to provide comfort by improving the microclimatic conditions (Idris et al, 2019;Almhafdy et al, 2013b; but also provided restorative environments that facilitated their well-being (Idris et al, 2018;Cooper Marcus and Barnes, 1995;Naderi and Shin, 2008). Regardless of the garden's positive effect on people's well-being, several scholars have argued that the outdoor gardens in Malaysian hospitals do not adequately consider their restorative functions (Shukor, 2007;Adnan, 2016).…”
Section: Introductionmentioning
confidence: 99%